Histopathology and selective biomarker expression in human meibomian glands. Issue 7 (4th October 2019) - Reneker, Lixing W; Irlmeier, Rebecca T; Shui, Ying-Bo; Liu, Ying; Huang, Andrew J W
Abstract : Background/aims: Meibomian gland dysfunction (MGD) is the most common form of evaporative dry eye disease, but its pathogenesis is poorly understood. This study examined the histopathological features of meibomian gland (MG) tissue from cadaver donors to identify potential pathogenic processes that underlie MGD in humans. Methods: Histological analyses was performed on the MGs in the tarsal plates dissected from four cadaver donors, two young and two old adults, including a 36-year-old female (36F) and three males aged 30, 63 and 64 years (30M, 63M and 64M). Results: The MGs of 36F displayed normal anatomy and structure, whereas the MGs of 30M showed severe ductal obstruction with mild distortion. The obstruction was caused by increased cytokeratin levels in association with hyperproliferation, but not hyperkeratinisation. In two older males, moderate to severe MG atrophy was noted. Cell proliferation was significantly reduced in the MG acini of the two older donors as measured by Ki67 labelling index (6.0%±3.4% and 7.9%±2.8% in 63M and 64M, respectively) when compared with that of the two younger donors (23.2%±5.5% and 16.9%±4.8% in 30M and 36F, respectively) (p<0.001). The expression patterns of meibocyte differentiation biomarkers were similar in the older and younger donors. Conclusion: Our histopathological study, based on a small sample size, suggests potentially distinct pathogenic mechanisms in MGD. In the young male adult, hyperproliferation and aberrant differentiation of the central ductal epithelia may lead to the obstruction by overproduced cytokeratins. In contrast, in older adults, decreased cell proliferation in acinar basal epithelia could be a contributing factor leading to MG glandular atrophy.